2009
DOI: 10.1029/2008jd009805
|View full text |Cite
|
Sign up to set email alerts
|

Influence of clouds on aerosol particle number concentrations in the upper troposphere

Abstract: This work investigates statistically the influence of clouds on aerosol particles in the upper troposphere, from the tropics to midlatitudes. More than 7500 particle concentration values, collected with the Civil Aircraft for the Regular Investigation of the Atmosphere Based on an Instrument Container, were analyzed for the occurrence of cloud contacts using backward trajectories and satellite images from the International Satellite Cloud Climatology Project. The majority of high‐altitude clouds over the Arabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 93 publications
0
47
0
1
Order By: Relevance
“…The remaining low particle counts may exist with high concentrations of precursor gases in a high actinic flux environment. Under such circumstances homogeneous nucleation of particles is theoretically possible, and has been observed (e.g., Perry and Hobbs, 1994;Hegg and Baker, 2009;Weigelt et al, 2009). Stohl et al (2007) in particular observed such behavior in SEA air transported to Europe.…”
Section: Convective Pumping and The Summer Monsoonal Anti-cyclonementioning
confidence: 99%
“…The remaining low particle counts may exist with high concentrations of precursor gases in a high actinic flux environment. Under such circumstances homogeneous nucleation of particles is theoretically possible, and has been observed (e.g., Perry and Hobbs, 1994;Hegg and Baker, 2009;Weigelt et al, 2009). Stohl et al (2007) in particular observed such behavior in SEA air transported to Europe.…”
Section: Convective Pumping and The Summer Monsoonal Anti-cyclonementioning
confidence: 99%
“…Of all observations, 88% were conducted in the troposphere at PV values below 1.5 PVU (10 −6 K kg −1 m 2 s −1 ). All back-trajectories along the flight route were checked for cloud contact during the previous 2 days using a FORTRAN algorithm (Weigelt et al, 2009) overlaying back-trajectories and satellite cloud images from the International Satellite Cloud Climatology Project (IS-CCP, http://isccp.giss.nasa.gov/).…”
Section: Methodsmentioning
confidence: 99%
“…Our understanding on FT nucleation relies heavily on modelling studies that have concentrated on either binary water-sulphuric acid or ion-induced nucleation (Yu et al,al., 2008;Kazil and Lovejoy, 2004;Kanawade and Tripathi, 2006). In a small number of studies the number concentrations of ultrafine (>3-5 nm) aerosol particles have been measured in the FT, with main emphasis put on the upper parts of the FT (Clarke, 1993;de Reus et al, 2000;Twohy et al, 2002;Benson et al, 2008;Weigelt et al, 2009;Young et al, 2007). Very few measurements of ion cluster size distributions from this region are available (Arnold, 2006), and observations of neutral clusters are entirely lacking.…”
Section: Introductionmentioning
confidence: 99%